2020
DOI: 10.1177/0963721420915866
|View full text |Cite
|
Sign up to set email alerts
|

Who Comes to Mind? Dynamic Construction of Social Networks

Abstract: Much remains unknown about moment-to-moment social-network cognition—that is, who comes to mind as we go about our day-to-day lives. Responding to this void, we describe the real-time construction of cognitive social networks. First, we outline the types of relational structures that comprise momentary networks, distinguishing the roles of personal relationships, social groups, and mental sets. Second, we discuss the cognitive mechanisms that determine which individuals are activated—and which are neglected—th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Specifically, we draw on emerging research showing that cognitive social networks may be conceptualized as dynamic rather than static and that their structures can be shaped by contextual and psychological factors (e.g., Menon and Smith 2014; Smith, Menon, and Thompson 2012). This dynamism is driven by network activation , a process in which the network an individual calls to mind can shift from moment to moment based on environmental or motivational cues that change who is salient in memory (Bayer, Lewis, and Stahl 2020). For example, Small, Pamphile, and McMahan (2015) showed that people’s core discussion network changed dynamically to fulfill their needs in the moment—and this influenced whom people sought out for social support.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, we draw on emerging research showing that cognitive social networks may be conceptualized as dynamic rather than static and that their structures can be shaped by contextual and psychological factors (e.g., Menon and Smith 2014; Smith, Menon, and Thompson 2012). This dynamism is driven by network activation , a process in which the network an individual calls to mind can shift from moment to moment based on environmental or motivational cues that change who is salient in memory (Bayer, Lewis, and Stahl 2020). For example, Small, Pamphile, and McMahan (2015) showed that people’s core discussion network changed dynamically to fulfill their needs in the moment—and this influenced whom people sought out for social support.…”
Section: Introductionmentioning
confidence: 99%
“…Bottom-up processes involve things in the environment that are not necessarily in one’s control or conscious awareness (Nisbett & Wilson, 1977) but that can shape to whom or what one is loyal when a loyalty conflicts with other loyalties or moral values. For example, the contexts in which people find themselves may shape which objects of loyalty they pay attention to and the strength of their loyalties (Bayer et al, 2020). A promotion at work may make salient certain loyalties, such as loyalty to one’s boss and organization.…”
Section: Integrated Perspective Of Loyaltymentioning
confidence: 99%
“…Bottom-up processes consist of things in our environment that are not necessarily in our control or conscious awareness (Nisbett & Wilson, 1977), but that can shape to whom or what we are loyal when loyalty conflicts with other loyalties or moral values. For example, the context in which a person finds themselves may shape which objects of loyalty they pay attention to (Bayer et al, 2020). A promotion at work may make salient certain loyalties, such as your loyalty to your boss and organization.…”
Section: Integrated Perspective Of Loyaltymentioning
confidence: 99%